An exploratory research of the usage level of e-commerce among SMEs in the west coast of Malaysia - Jetol Bolongkikit; Joe Henry Obit; Joyce Georgina Asing; Geoffrey Harvey Tanakinjal (JIBC Publisher, 2006)
Previous studies have indicated that e-commerce development offers a promising way for business to meet the challenges of the ever-changing environment. It provides effective and efficient ways, such as buyers can gather information rapidly about the availability of the products or services, evaluate, or negotiate with vendors. However, previous studies on Small and Medium Enterprises (SMEs) in Malaysia have shown that the application of e-commerce is still at its infancy. Thus, this study investigates the usage level of e-commerce application for the SMEs in West Coast of Sabah, Malaysia. This achieved by circulating a set of questionnaire to examine the awareness and adoption of e-commerce application by the SMEs, and recognize the impeding factors to adopt e-commerce and the perception of e-commerce benefits towards incorporating ecommerce in their business. The study found that the awareness and adoption level among the SMEs are still in its infancy, although the potential benefits were perceived to be important.